THE EFFECT OF MIG WELDING CURRENT VARIATIONS ON THE HARDNESS AND MICRO-STRUCTURE TESTS OF ST 37 STEEL - Triyoko Budi Wibowo (ROTOR, 2025)
This study investigates the effect of welding current variations on the hardness and microstructure of ST 37 steel using Metal Inert Gas (MIG) welding. The experimental method was applied, where three current variations (100 A, 110 A, and 120 A) were used to weld ST 37 steel specimens. The specimens were then tested for hardness using the Vickers hardness test and examined for microstructural changes using an optical microscope. The results show that higher welding currents increase hardness, with the highest Vickers hardness value recorded in the heat-affected zone (HAZ) at 120 A (399.56 VHN). Microstructural analysis revealed the presence of ferrite and pearlite phases, with a higher pearlite fraction in the weld metal and HAZ, leading to increased hardness. This study provides insight into optimizing welding parameters to enhance the mechanical properties of welded steel structures. Keywords: MIG welding, welding current, hardness test, ST 37 steel, microstructure